2010
DOI: 10.3141/2167-05
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Laboratory Evaluation and Field Construction of Recycled Concrete Materials for Use in Road Substructures

Abstract: Given the renewal of urban infrastructure and the increased costs of landfilling concrete rubble materials, opportunities exist to optimize the reclamation and recycling of portland cement concrete (PCC) and hot-mix asphalt concrete (HMAC) rubble through their innovative use in road rehabilitation. The primary objective of this study was to demonstrate the ability to reclaim, process, and recycle stockpiled concrete materials to provide improved structural mechanistic–climatic material properties and to meet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…The granular base layer is an important component in pavement structure designs, as it protects the subgrade and provides drainage for the pavement structure (2). Areas with concentrated truck haul and poor-quality aggregate have experienced road performance that Crushed PCC and RAP can be used in a pavement structure as fill (subbase), drainage layer, and base layer (1)(2)(3)(5)(6)(7). Saskatchewan agencies have undertaken efforts to recycle and reuse concrete aggregates.…”
Section: Modeling In Situ Performance Of Cement-stabilized Granular Base Layers Of Urban Roadsmentioning
confidence: 99%
See 2 more Smart Citations
“…The granular base layer is an important component in pavement structure designs, as it protects the subgrade and provides drainage for the pavement structure (2). Areas with concentrated truck haul and poor-quality aggregate have experienced road performance that Crushed PCC and RAP can be used in a pavement structure as fill (subbase), drainage layer, and base layer (1)(2)(3)(5)(6)(7). Saskatchewan agencies have undertaken efforts to recycle and reuse concrete aggregates.…”
Section: Modeling In Situ Performance Of Cement-stabilized Granular Base Layers Of Urban Roadsmentioning
confidence: 99%
“…In Saskatchewan, crushed PCC and RAP material have been used as base material, backfill material, drainage rock, and subbase material. Using recycled aggregates in road construction has many environmental and economic benefits: conservation of virgin aggregates, reduction in the impact on landfills, limitations on haul distance when crushed locally, reduction in disposal and transportation costs, and reduction in overall cost compared with procurement of virgin aggregates (7). In many studies, the performance of recycled PCC in a base layer has been comparable to that of virgin granular aggregate (8-11).…”
Section: Modeling In Situ Performance Of Cement-stabilized Granular Base Layers Of Urban Roadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to available literature e.g., [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], RCA has been used in the base course and subbase course of pavements over the last two decades. However, few research studies [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] have reported the utilization of RCA in HMA.…”
Section: Introductionmentioning
confidence: 99%
“…Among the recycled aggregates that can be utilized in asphalt mixture, RCA obtained from construction and demolition waste constitute a major part of generated solid waste as a result of renovation and construction projects. Referring to literature survey (e.g., Arulrajah [38][39][40][41][42]. Accordingly, in this research, the properties of RCA have been thoroughly evaluated through the laboratory investigation and tests.…”
Section: Introductionmentioning
confidence: 99%